2021
DOI: 10.1186/s44147-021-00019-7
|View full text |Cite
|
Sign up to set email alerts
|

A new technological approach to the granulation of slag melts of ferrous metallurgy: obtaining glassy fine-grained granules of improved quality

Abstract: The technological factors required to improve the operational properties of granulated metallurgical slags demanded in the building industry have been analyzed. In order to satisfy these factors, a new technology for hydro-vacuum granulation of slag melts (HVG) has been developed. It is shown that the main advantage of the proposed HVG process is the provision of forced high-speed vortex convection of water, with the effect of vertical suction, crushing, and degassing of the three-phase (water–slag granules–wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…As a result of experimental studies, it was also found that the use of hydrovacuum dispersion method is also highly effective for dispersing slag melts and obtaining from them amorphous solidified (glassy) powdery raw materials with high hydraulic activity, suitable for the production of construction (Portland) cement [29]. In the case of hydrovacuum dispersion of slag, the rational weight ratio "slag: water" was 1:18.…”
Section: Research Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result of experimental studies, it was also found that the use of hydrovacuum dispersion method is also highly effective for dispersing slag melts and obtaining from them amorphous solidified (glassy) powdery raw materials with high hydraulic activity, suitable for the production of construction (Portland) cement [29]. In the case of hydrovacuum dispersion of slag, the rational weight ratio "slag: water" was 1:18.…”
Section: Research Results and Discussionmentioning
confidence: 99%
“…As a rational solution to the above problem, we chose the way of improving the design of the pilot unit [22] and expanding the functional capabilities of the innovative method of hydrovacuum dispersion of alloys [23], specially developed by us earlier for the above purpose. The general arrangement of the new dispersion unit and its main process juncture is illustrated in Figure 1.…”
Section: Research Methodology and Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main factor limiting the application of direct alloying technology in the conditions of out-offurnace processing, steel and alloys, is the increase in the amount of slag in the ladle [16]. Consequently, there is a necessity to perform an additional operation of slag downloading from the ladle, which slightly complicates the implementation of the technology, but by putting into operation the innovative installation of hydro-vacuum vertical suction and slag granulation [17], developed by us, this problem can be solved with minimum energy costs and operating time. According to the noted study [16] higher performance can be achieved by applying direct alloying technology under oxidizing conditions in order to increase the residual manganese content in the metal before out-of-furnace treatment.…”
Section: Current State Of the Problemmentioning
confidence: 99%
“…inclusions. The slurry formed with water cools down instantly without generating vapor, smoke or specific noise [4,5].…”
mentioning
confidence: 99%